Sociodemographic predictors of postpartum post-traumatic stress symptoms—cross-sectional study - Burdecka, Julia Marianna; Szablewska, Anna Weronika (Frontiers in Psychology, 2025)
BackgroundPostpartum psychological distress, including depression and post-traumatic stress disorder (PP-PTSD), poses serious risks for maternal and child well-being. The role of sociodemographic predictors remains less understood, particularly in Poland.MethodsAn observational, cross-sectional study was conducted among 273 Polish women. Sociodemographic and obstetric information was obtained using a self-designed online questionnaire. Symptoms of depression, anxiety, and stress were measured using the DASS-21, and post-traumatic stress symptoms were assessed with the PTSD-8 scale. Multivariable logistic regression analyses were conducted to examine associations between psychological outcomes and sociodemographic predictors.ResultsYounger maternal age was linked to higher anxiety, informal relationship status to greater stress, and financial hardship to both stress and depression. Rural residence was associated with elevated anxiety and PTSD symptoms, while non-physiological delivery increased the likelihood of PTSD. Other factors, including education, parity, and miscarriage history, were not significantly associated with psychological outcomes.ConclusionSociodemographic and obstetric factors influence postpartum mental health. Targeted screening and support are needed for women facing economic strain, unstable relationships, rural disadvantage, or traumatic birth experiences. Development of culturally adapted Polish screening tools and improved access to trauma-informed perinatal care are recommended.